2022
DOI: 10.1111/jfpe.14200
|View full text |Cite
|
Sign up to set email alerts
|

Development of white finger millet probiotic beverage using Lactocaseibacillus rhamnosus (LGG): Process optimization and study of physicochemical and nutritional properties

Abstract: White finger millet (WFM) is a repository of vital nutrients and minerals. This study aims to develop the white finger probiotic beverage, optimize the ingredients level for the formulation, and study the physiochemical and nutritional properties of the formulated vegan WFM probiotic beverage (WFMPB). The optimum condition for the development of WFMPB was obtained by Box–Behnken design. The independent variable like WFM flour (10–14% w/v), microbial inoculum (1–5% v/v), and sugar (5–15% w/v), and their impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The findings are similar to the outcomes stated by Gong et al (2020) , who found that potato flour lightness intensity gradually rose with fermenting duration. Our findings are corroborated by a recent study by Navyashree, Buvaneswaran, Sunil, Rawson, and Natarajan (2022) , who reported L* and b* value color profiles in the white finger millet probiotic beverage that are similar to the range obtained in the current study. In the present study, no significant changes were measured for a* value in fermented samples compared to the control, except in the LGG (8 h) sample.…”
Section: Resultssupporting
confidence: 93%
“…The findings are similar to the outcomes stated by Gong et al (2020) , who found that potato flour lightness intensity gradually rose with fermenting duration. Our findings are corroborated by a recent study by Navyashree, Buvaneswaran, Sunil, Rawson, and Natarajan (2022) , who reported L* and b* value color profiles in the white finger millet probiotic beverage that are similar to the range obtained in the current study. In the present study, no significant changes were measured for a* value in fermented samples compared to the control, except in the LGG (8 h) sample.…”
Section: Resultssupporting
confidence: 93%
“…Besides, combinations of different millets have also been used to prepare multi‐millet‐based beverages (Arya & Shakya, 2021; Kiruthika et al., 2018; Kumar et al., 2016). In addition, some studies have also been done on the development of millet‐based probiotic beverages utilizing different varieties of finger millet and other processing techniques such as ultrasonication and freeze‐drying (Meena et al., 2023; Navyashree et al., 2023; Vila‐Real et al., 2022). However, to the best of our knowledge, no work has been done to optimize the soaking time and temperature of finger millet for extraction or preparation of the beverage.…”
Section: Introductionmentioning
confidence: 99%
“…It contributes to the reduction of antinutrients by the degradation and conversion of the antinutrients into smaller units using mobilized enzymatic activity during the fermentation and intensifies human intestinal health. Different Lactobacillus species such as L. acidophilus , L. fermentum , L. paracasei , L. plantarum , and L. casei have been explored for the development of various fermented plant-based milk. The lactobacillus strains used are nontoxic, nonpathogenic, and have high adherence to the intestinal mucosa. Hence, it could be used for the probiotic fermentation of finger millet products. The previously reported work was focused on the development of probiotic finger millet milk using Lactobacillus casei and Lactobacillus rhamnosus with different process protocols.…”
Section: Introductionmentioning
confidence: 99%